Baseline quality of life in people with hip fracture: results from the multicentre WHiTE cohort study. Issue 8 (August 2020) - Parsons, Nick R; Costa, Matthew L; Achten, Juul; Griffin, Xavier L
Abstract : Aims: To assess the variation in pre-fracture quality of life (QoL) within the UK hip fracture population, and quantify the nature and strength of associations between QoL and other routinely collected patient characteristics and treatment choices. Methods: The World Hip Trauma Evaluation (WHiTE) study, an observational cohort study of UK hip fracture patients, collects a range of routine data and a health-related QoL score (EuroQol five-dimension questionnaire (EQ-5D)). Pre-fracture QoL data are summarized and statistical models fitted to understand associations between QoL, patient characteristics, fracture types, and operations. Results: Fitting a multiple linear regression model indicated that 36.5% of the variance in pre-fracture EQ-5D scores was explained by routinely collected patient characteristics: sex (0.14%), age (0.17%), American Society of Anesthesiologists (ASA) score (0.73%), Abbreviated Mental Test Score (AMTS; 1.3%), pre-fracture mobility (11.2%), and EQ-5D respondent (participant, relative, or carer; 23.0%). There was considerable variation in pre-fracture EQ-5D scores between operations within fracture types. Participants with trochanteric fractures reported statistically significant but not clinically relevant lower pre-fracture QoL than those with intracapsular fractures. Participants with intracapsular fractures treated with internal fixation or total hip arthroplasty (THA) reported better QoL than those treated with hemiarthroplasty with the overall fittest group receiving THA. Conclusion: Pre-fracture QoL varies considerably between hip fracture patients; it is generally higher in younger than older patients, patients with better mobility, and those patients who live more independently. Pre-fracture QoL is significantly associated with a range of patient characteristics (e.g. age, mobility, residency). These data explain ~35% of the variation in QoL. Cite this article: Bone Joint Res 2020;9(8):468–476.